Uncommon Rhythms: Rupture and Retreat in Inner-City Johannesburg - Matthew Wilhelm-Solomon (Cidades, Comunidades e Território)
This paper argues that the rhythms of life in precarious urban areas of inner-city Johannesburg are characterised by a series of chronic shocks involving fire, police raids, immigration raids and evictions. Against the backdrop of such shocks, inner-city residents, particularly the residents of unlawful occupations, attempt to form bonds of care and support among themselves. Based on long-term fieldwork, over several periods, in the area between 2010 and 2023, the paper shows that these everyday rhythms of commoning – the affective labour of forming social relations in the interstices of the state ensemble and real estate markets – are in constant play with forms of uncommoning – emergent fissures and divisions in the city. However, forms of major shock radically corrode the bases of commoning practices and dissemble everyday rhythms. In this paper, I develop the concept of ‘uncommon rhythms’ to indicate both everyday divisions and divergences and the recurrent, but unpredictable, forms of shock that shape life among precarious communities in the inner-city. I argue that secure accommodation and spaces of retreat are a necessary precondition for sustaining commoning practices.